"My problems aren't severe enough to seek help": Stress levels and use of mental health supports by Canadian hospital employees during the COVID-19 pandemic. Issue 2 (February 2022) - Ménard, Amy Dana; Soucie, Kendall; Freeman, Laurie A.; Ralph, Jody L.
Highlights: Overall levels of depression, stress, and anxiety were mild in healthcare employees surveyed. A significant minority of participants reported feeling very or extremely stressed (13.5%−21.8%). The use of formal mental health supports was very low (< 10%). The use of informal mental health supports was very high (> 75%). The most common reason for not using supports was "problems not severe enough". Abstract: Due to the unique set of stressors associated with the COVID-19 pandemic, healthcare workers in acute care settings may be facing elevated rates of mental health symptomatology. The purpose of this study was to assess levels of depression, anxiety, and stress in a sample of healthcare employees working in hospitals and their use of formal and informal mental health supports. Data was gathered over a three-week period in December 2020 as COVID cases began to rise sharply in Ontario, Canada. Results from an online survey of 650 healthcare employees suggested that overall levels of depression, anxiety, and stress were mild. However, a significant minority of participants reported severe or extremely severe levels of depression (14.4%), anxiety (21.8%), and stress (13.5%). Levels of distress were higher among women, younger participants, those who did not work directly with COVID+ patients, and those who were redeployed. Use of formal mental health supports (e.g., Employee Assistance Plans, teletherapy) was very low (<10%), with the most frequently-reported reason for not using supports being "problems not severe enough to require this service". Implications are considered for healthcare policy decisions as hospital systems attempt to address the mental health needs of their employees.